Thermal-hydraulic analysis of fuel rod of a TRIGA Mark II research reactor - Shafiqul Islam, Md; Hossain Khan, Abid (International Journal of Engineering and Technology, 2020)
In this work, the feasibility of employing â€œSingle Flow Channel Analysisâ€ technique for obtaining the thermal-hydraulic behavior of a TRIGA Mark II research reactor has been studied. Two different simulation methods have been investigated for this purpose; one in which there is no variation in volumetric heat generation along the fuel axis and the other in which there is variation. A hot rod factor of 1.70 has been taken. Results obtained from simulation methods have been compared with both theoretical results and experimental data provided by the manufacturers. Results show that data generated from both simulation methods are more accurate compared to theoretical calculations. Also, the simulation method exempting variation of heat generation has predicted maximum temperature of the fuel centerline just above 750 oC, which is sufficiently accurate. However, temperatures obtained at different axial and radial locations are not close to the experimental values. On the other hand, the simulation technique in which variation of heat generation exists has been able to provide temperature profiles inside the fuel rod and cladding surface almost identical to the experimental values. However, temperature profile of the fuel outer surface is found to be quite different from experimental values.Â Â
Keywords: Hot Rod Factor; Research Reactor; Temperature Distribution; Thermal-Hydraulics.